2021
DOI: 10.1186/s13567-021-00935-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Glaesserella parasuis strains isolated from North America, Europe and Asia by serotyping PCR and LS-PCR

Abstract: Glaesserella parasuis strains were characterized by serotyping PCR, vtaA virulence marker Leader Sequence (LS)-PCR, clinical significance, and geographic region. Overall, the serovars 4, 5/12, 7, 1, and 13 were the most commonly detected. Serovars of greatest clinical relevance were systemic isolates that had a higher probability of being serovar 5/12, 13, or 7. In comparison, pulmonary isolates had a higher likelihood of being serovars 2, 4, 7, or 14. Serovars 5/12 and 13 have previously been considered disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
5
15
0
Order By: Relevance
“…Nonetheless, the majority of the isolates described in this study, which were obtained from two major pig producing states in Malaysia (Perak and Selangor), were detected to be serotype 5 or 12. This is consistent to the predominance of serotype 5 or 12 found in North America, Europe and Asia [ 37 ]. For a better overview of the G. parasuis serotypic distribution within the country, the current study may be expanded to include all pig producing states in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, the majority of the isolates described in this study, which were obtained from two major pig producing states in Malaysia (Perak and Selangor), were detected to be serotype 5 or 12. This is consistent to the predominance of serotype 5 or 12 found in North America, Europe and Asia [ 37 ]. For a better overview of the G. parasuis serotypic distribution within the country, the current study may be expanded to include all pig producing states in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…Today this list has been expanded as we have demonstrated for the first time the presence of virulent strains of G. parasuis SV7 causing GD in Brazilian pig farms. The global circulation of virulent strains typed as SV7 has been demonstrated in different studies [ 33 , 34 ], which highlights the importance of this serovar as the causative agent of GD.…”
Section: Resultsmentioning
confidence: 99%
“…Serotype 4 is also the most prevalent serotype in China in pigs suffering from Glässer’s disease [ 31 ], while in nasal swabs of healthy pigs most frequently serotype 7 (20%) and 3 (15%) were detected [ 32 ]. In a recent study concerning the distribution of Gps serotypes in different regions of the world, serotype 5/12 was the most common sort in Canada, China and Vietnam (22–31%) and the second most common sort in Europe (14%) behind serotype 4 (17%) [ 33 ]. These findings were comparable to those in our study, although a high proportion of Gps had been isolated from the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were comparable to those in our study, although a high proportion of Gps had been isolated from the respiratory tract. In most studies, Gps serotype 5 was found more frequently in systemic internal sites [ 33 ]. In our study, more than 90% of the Gps serotype 5 strains were isolated from the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%